Growth Rate of Plasmodium falciparum: Analysis of Parasite Growth Data From Malaria Volunteer Infection Studies. (4th November 2019) - Wockner, Leesa F; Hoffmann, Isabell; Webb, Lachlan; Mordmüller, Benjamin; Murphy, Sean C; Kublin, James G; O'Rourke, Peter; McCarthy, James S; Marquart, Louise
Abstract: Background: Growth rate of malaria parasites in the blood of infected subjects is an important measure of efficacy of drugs and vaccines. Methods: We used log-linear and sine-wave models to estimate the parasite growth rate of the 3D7 strain of Plasmodium falciparum using data from 177 subjects from 14 induced blood stage malaria (IBSM) studies conducted at QIMR Berghofer. We estimated parasite multiplication rate per 48 hours (PMR48 ), PMR per life-cycle (PMRLC ), and parasite life-cycle duration. We compared these parameters to those from studies conducted elsewhere with infections induced by IBSM (n = 66), sporozoites via mosquito bite (n = 336), or injection (n = 51). Results: The parasite growth rate of 3D7 in QIMR Berghofer studies was 0.75/day (95% confidence interval [CI], .73–.77/day), PMR48 was 31.9 (95% CI, 28.7–35.4), PMRLC was 16.4 (95% CI, 15.1–17.8), and parasite life-cycle was 38.8 hours (95% CI, 38.3–39.2 hours). These parameters were similar to estimates from IBSM studies elsewhere (0.71/day, 95% CI, .67–.75/day; PMR48 26.6, 95% CI, 22.2–31.8) but significantly higher ( P <  .001) than in sporozoite studies (0.47/day, 95% CI, .43–.50/day; PMR48 8.6, 95% CI, 7.3–10.1). Conclusions: Parasite growth rates were similar across different IBSM studies and higher than infections induced by sporozoite. Abstract : Growth rates of Plasmodium falciparum 3D7 strain in 177 subjects from 14 studies (0.75/day) were similar across induced blood stage malaria studies conducted elsewhere (0.71/day) and higher than infections induced by sporozoite (0.47/day), but parasite life-cycles were similar (38.8 hours).